How familiar are clinician teammates in the emergency department?. Issue 4 (18th December 2013) - Patterson, P Daniel; Pfeiffer, Anthony J; Lave, Judith R; Weaver, Matthew D; Abebe, Kaleab; Krackhardt, David; Arnold, Robert M; Yealy, Donald M
Abstract : Objectives: Lack of familiarity between teammates is linked to worsened safety in high risk settings. The emergency department (ED) is a high risk healthcare setting where unfamiliar teams are created by diversity in clinician shift schedules and flexibility in clinician movement across the department. We sought to characterise familiarity between clinician teammates in one urban teaching hospital ED over a 22 week study period. Methods: We used a retrospective study design of shift scheduling data to calculate the mean weekly hours of familiarity between teammates at the dyadic level, and the proportion of clinicians with a minimum of 2, 5, 10 and 20 h of familiarity at any given hour during the study period. Results: Mean weekly hours of familiarity between ED clinician dyads was 2 h (SD 1.5). At any given hour over the study period, the proportions of clinicians with a minimum of 2, 5, 10 and 20 h of familiarity were 80%, 51%, 27% and 0.8%, respectively. Conclusions: In our study, few clinicians could be described as having a high level of familiarity with teammates. The limited familiarity between ED clinicians identified in this study may be a natural feature of ED care delivery in academic settings. We provide a template for measurement of ED team familiarity.